Membangun Kesadaran Siswa untuk Mencuci Tangan Melalui Eksperimen Sabun dan Merica - Syifa Retno Putri Lestari; Azmiyah Rihadatul Aisy; Iqbal Saputra; Fikri Fathur Rohman (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2024)
Abstract Real work lecture activities (KKN) for UIN Sunan Gunung Djati Bandung students which took place in Padamulya Village, Majalaya District, Bandung Regency in the field of education in collaboration with 5th grade students at Padamulya 2 Elementary School to provide socialization to students regarding the importance of washing their hands with soap because they saw lack of awareness of students in washing their hands with soap before eating. Therefore, carrying out this activity can form student awareness through interesting and creative delivery, so that students can understand directly. The method used is through demonstration and experimentation with students. Forms of activities include delivering material, demonstrating proper hand washing, sticking pamphlets, experiments with soap and pepper, and washing hands together. The results of this real work lecture (KKN) activity can increase students' knowledge and knowledge. Students gain experience and social knowledge directly by going directly to the field and students can absorb the knowledge that students have as an increase in insight for preparation in everyday life.